Prioritization of Local Livelihood Promotion Strategies with the Approach of Sustainable Exploitation of Natural Resources Based on SWOT-ANP Model in Bagherabad Village of Kurdistan - Iman Islami; Asghar Farajollahi (جغرافیا و آمایش شهری منطقه‌ای, 2022)
Planning to improve the livelihoods and incomes of rural households is considered as an important and effective foundation in achieving sustainable development goals. Strategies for improving livelihoods of Bagherabad village of Sanandaj city were investigated based on natural resources approaches. The statistical population included residents of Bagherabad village and expert in rural affairs of study area that the sample size was 255 villagers and 42 experts. The questionnaire was the important tool for gathering of information and SWOT model was used to analyze the data and appropriate strategies. In order to prioritize the most important factors affecting the improvement of livelihood in the region, the Analytic Network Process (ANP) model was used in this study. Natural crisis and related threats to rural livelihood, such as drought and flood, was the most important threat according to villagers and experts with relative weights of 91.11 and 80, respectively. Existence educated human resources and their training and use of them in rural development is the most important opportunity to improve the livelihood from the viewpoint of experts and residents with relative weights of 81.78 and 87.11, respectively. Existence educated human and their training and use of them in rural development is the most important opportunity to improve the livelihood from the viewpoint of experts and residents with relative weights of 81.78 and 87.11, respectively. Strategy for improving the livelihood in study area obtained defensive strategy. This strategy is planned based on training and promotion of optimal utilization practices of natural lands and water resources, new technologies of agriculture, livestock and horticulture especially in drought conditions, improvement of rural infrastructure facilities and relying on ecotourism potentials and handicraft. The results of a network of factors showed that human-educational, climatic-geographical, economic-financial factors will be the most influential factors in the development and promotion of rural livelihood in the study area, respectively. This study recommends the use of the SWOT-ANP method as a way to identify important socio-economic-ecological axes along with determining the main strategy of promoting rural areas in the form of major capitals with the most stability and adaptively.